1982
DOI: 10.2307/3898394
|View full text |Cite
|
Sign up to set email alerts
|

Vegetative Response to Clearcutting and Chopping in a North Florida Flatwoods Forest

Abstract: Selected naturally regenerated flatwoods forests were clearcut and chopped in preparing a large, long-term study of the effects of several multiple-use management practices on forest vegetation and wildlife. Early effects of clearcutting and chopping on understory vegetation are reported here. Clearcutting and chopping reduced woody understory coverage from 66 to 18% of surface area. Common gallberry and saw-palmetto were reduced by 75 and 8!9& respectively. Herbaceous species frequency was htcreased: Panicurn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 3 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Rodriguez 2011), high light levels (Means 1997), minimally required edaphic and hydrological conditions (Carr et al 2010), and absence of severe soil disturbance (Moore et al 1982), our study likely would have shown a decrease in the originally planted population under other conditions. Understanding the specific management conditions required to increase populations of plants with particular life historic characteristics should be a continued focus of restoration research.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Rodriguez 2011), high light levels (Means 1997), minimally required edaphic and hydrological conditions (Carr et al 2010), and absence of severe soil disturbance (Moore et al 1982), our study likely would have shown a decrease in the originally planted population under other conditions. Understanding the specific management conditions required to increase populations of plants with particular life historic characteristics should be a continued focus of restoration research.…”
Section: Discussionmentioning
confidence: 79%
“…Under the conditions studied, wiregrass showed the fundamental characteristics of a species predicted to be successful in restoration efforts following low‐density planting, including strong competitive ability, capacity to colonize gaps in vegetation, ability to undergo vegetative reproduction, and a relatively wide edaphic niche as suggested by the differences between source sites (Pywell et al 2003). However, whereas wiregrass shows the capacity to gradually become dominant under the appropriate fire frequency and season (Mulligan & Kirkman 2002; Rodriguez 2011), high light levels (Means 1997), minimally required edaphic and hydrological conditions (Carr et al 2010), and absence of severe soil disturbance (Moore et al 1982), our study likely would have shown a decrease in the originally planted population under other conditions. Understanding the specific management conditions required to increase populations of plants with particular life historic characteristics should be a continued focus of restoration research.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Rare species influence the perpetuation of some desirable community components more than do abundant species and are frequently suggested as being required in order to maintain biological diversity. Although these diversity assessments are indifferent to plant names, graphical methods for examining individual species responses to treatment are available (Moore et al 1982a(Moore et al , 1982b.…”
Section: Effects On Diversity Profilesmentioning
confidence: 99%